Inhibitory effect of herbal compounds on the Oxygen-insensitive NADPH nitro reductase enzyme of metronidazole-resistant Helicobacter pylori (Sciences of Phytochemistry, 2023)
Helicobacter pylori is a significant risk factor for chronic gastritis, gastric ulcers, and gastric cancer. The purpose of this article is to investigate the potential impact of fifty herbal compounds derived from Ginger and Parsley plants, known for their antibacterial properties on the Oxygen-insensitive NADPH nitro reductase enzyme of metronidazole-resistant H. pylori. In the present study, the information on the structure of compounds, the H. pylori resistant to metronidazole enzyme, myristicin, and shogaol derivatives were obtained from databases such as ZINC15, RCSB (Protein Data Bank), and PubChem, respectively. Finally, molecular docking was performed with iGemdock2.1 and Molegro Virtual Docker. After molecular docking, four out of the fifty phytocompounds showed the lowest energy and the highest number of interactions with the amino acids at the binding sites. Among these four phytocompounds, the best phytocompound was N-Vanillyloctanamide derived from Ginger. Our molecular docking study suggests that ginger can be introduced as a potential candidate to inhibit the growth of H. pylori.